(untitled) (Experimental biology, 2026)
Polyphenols constitute an important component of the plant antioxidant defense system and are valuable substances for human health. The aim of the study was to evaluate the effect of sowing dates on polyphenol accumulation in the leaves and seeds of soybean cultivars differing in maturity group, as well as the association of these parameters with polyphenol oxidase activity at the pod formation stage. Analysis of polyphenol content at early and late stages of soybean reproductive development allows differentiation of cultivars, breeding lines and germplasm collections based on technological traits and nutritional value. Polyphenol content was determined using the Folin-Ciocalteu reagent. Polyphenol oxidase activity was determined by a photometric method, using pyrocatechol as a substrate. In terms of developmental timing, the genotypes ranged from early-maturing to extremely late-maturing forms under standard sowing dates and from ultra-early to late-maturing forms under delayed sowing. Determination of polyphenol content in soybean leaves at the R5 stage revealed a tendency toward a decrease in their concentration with increasing length of the growing season under both standard and delayed sowing dates. At the stage of full maturity under both sowing dates polyphenol levels increased in relation to maturity group. Early-maturing forms were characterized by lower polyphenol oxidase activity compared with late-maturing forms. The correlation between polyphenol content and leaf polyphenol oxidase activity was negative. The conducted studies made it possible to differentiate 170 soybean genotypes according to polyphenol accumulation at different stages of reproductive development, depending on maturity group and sowing dates.